(untitled) (Journal of Engineering, 2024)
The grouted ground anchor is the most used geotechnical element to transfer the tension load from the superstructure or the soil mass in front of the potential failure surface (active zone) to a deeper, efficient soil layer for its reliability and feasibility. It was originally constructed by inserting the tendon, usually a steel strand, into an already drilled borehole filled with cement grout. It was successfully used in the Cheurfas dam in Algeria in (1934). According to the load transfer mechanism, there are two types of ground anchors: tension-type and compression-type. The names of these two types of anchors refer to the developed stresses in the grouted body. The present work presents a literature survey about the load transfer mechanism for both types of anchors: tension and compression embedded in granular soil. Many factors affecting the load transfer mechanism have been reviewed. The main factor affecting the load transfer mechanism is the confining pressure of the borehole. The recently developed methods of estimating the ultimate pullout capacity of the anchor have been reviewed and discussed.